Effective Performance Of Lead Apron As One Protective Equipment In Radiation - Yeti Kartikasari; Siti Masrochah (Jurnal Riset Kesehatan, 2012)
This study is a survey research, with a sample Hospital in Semarang with the number of samples apron as much as 49 pieces. Methods of research done by observation, measurement and documentation. Measurements were made using flouroskopi to identify defect lead apron. The data analysis is done by analyzing the percentage of damaged apron on the entire sample, categorized  reject level of disability if the leakage obtained apron greater than 670 mm2. Care Lead Apron in Radiology Installation varies by hanging up and placed horizontally. Situation and Function Lead aprons as protective of radiation exposure in the City Semarang apron 44 of 49 samples within safe limits (less disability 670 mm2) and 5 aprons in the experience of disability (more than 670 mm2) and must rejected. Lead apron owned Radiology Installation in Semarang has a thickness of 0.25 mmPb to the lowest voltage tubes up to 100 kV, and 0.35 mmPb - 0,5 mmPb for tube voltages above 100 kV.